PLATON: KEMUNGKINAN “POLIS-DIKAIOS” DAN “INDIVIDU-DIKAIOS” (BUKU V) - Oktovianus Kosat (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2017)
“For what we laid down in the beginning as universal requirement when we were founding our city, this i thing, or some form of this, is justice. And what we did lay down, and often said, if you recall, was that each one man must perform one social service in the state for which his nature was best adapted. And we said again that to do one’s own business and not to be a busybody is justice”.